Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Influencer Marketing terhadap Kepuasan Pelanggan pada Sego Sambel Merdeka - Qastalano, Rezha Isyraqi; Nugroho, Rizky Adhitya; Bahanan, Muhammad (LPPM Universitas Nusa Mandiri, 2025)
Indonesia’s culinary scenes today has grown and expanded significantly in each region. Increasing culinary demand affects on customer satisfaction. The study’s purpose is to ascertain impact of product quality, service quality, and influencer marketing on customer satisfaction of Sego Sambel Merdeka on Mojokerto which is secured to raise sales, share of the market, and competitive edge. The approach of this study is quantitative by using respondent questionnaires using convenience sampling of 50 respondents. The study’s hypothesis test used the method of multivariate linear regression. The findings of this study indicates results of the validity and realibility tests which have been processed are valid and reliable. The traditional assumption test in this study revealed a normal distribution and no symptoms of multicollinearity and heteroskedasticity occurred. The determination test revealed that 41.2% of the variability of customer satisfaction was impacted by product quality, service quality, and influencer marketing, with a regression equation of Y = -1.689 + 0.336X1 + 0.190X2 + 0.771X3 + e which showed a positive influence. The conclusion obtained on this research is that product quality and influencer marketing have significantly impact on customer satisfaction, but service quality have not significantly impact on customer satisfaction, so in this research, it is implied that Sego Sambel Merdeka business owners are advised to focus more on improving product quality and maximizing influencer marketing strategies, even though the quality of service is not significant in this study periodic evaluation to ensure adequate service standards.